Clinical Features and Surgical Treatment of Synchronous Multiple Primary Lung Adenocarcinomas With Different EGFR Mutations - Qu, Rirong; Ye, Fan; Tu, Dehao; Cai, Yixin; Fu, Xiangning (Frontiers in Oncology, 2022)
Background: With the popularity of lung cancer screening and advances in imaging technology, more and more synchronous multiple primary lung adenocarcinomas (SMPLA) are being diagnosed clinically, however, the clinical characteristics and prognosis of SMPLA with different EGFR mutations remains unclear. We aimed to explore clinical features and surgical outcomes of these patients to aid in the diagnosis and treatment of SMPLA. Methods：Medical records of patients with different EGFR mutations who have been diagnosed as SMPLA and underwent surgical resection from March 2015 to December 2019 were retrospectively analyzed. Clinical characteristics, surgical outcomes, recurrence-free survival (RFS) and overall survival (OS) were investigated. Results：A total of 70 patients ( 68.6% female and 77.1% non-somkers) were included. Total of 161 lesions in all patients, 84.4% were ground-glass opacity (GGO) lesions. EGFR mutations were detected in 108 lesions, most of which were L858R (35.4%) and 19Del (20.5%). The mutation rate of mixed GGO is significantly higher than that of pure GGO and solid nodules (SN); the mutation rate of invasive adenocarcinoma is significantly higher than that of other histology subtypes; the mutation rate of lesions 20 mm was significantly higher than that of 20 mm. However, there is no significant difference in the mutation rate of specific driver gene between different radiological features, pathological characteristics and sizes. After a median follow-up time of 29 months, the 3-year OS and RFS were 94.4% and 86.0%, respectively. Conclusions：A high discordance of EGFR mutations were identified between tumors in patients with SMPLA. Synchronous multiple lung adenocarcinomas with predominantly multiple GGO should be considered as SMPLA, and surgery may be aggressively performed for these patients due to a good prognosis.